RESOR KLAYAR DENGAN PENDEKATAN FENOMENOLOGI ARSITEKTUR DI KAWASAN WISATA PANTAI KLAYAR PACITAN - Stefany Windira Pramudita; Titis Srimuda Pitana; Sri Yuliani (ARSITEKTURA, 2016)
The background in designing Klayar Resort in Pacitan is based on the natural and cultural potential and the existed issue of cultural shift. The phenomenology architecture study is applied to grasp the phenomena where the architect acts as the instrument. The design goal is to represent a recreation place in creating a temporary living space, within the phenomenology comprehension of the physical and non-physical identification, where the place is capable of resurrecting the spirit of place with the identity that has already been formed. It is expected that the tourists can make a self-orientation and self-identification with the surrounding by understanding the actual phenomena. The design issues that will be completed covers the determination of society and tourists’ activities, the need and circulation space, the selection and processing of the site, the determination of design for each building in accordance with the phenomenology study. The obtained result will be a shelter in a form of a resort that is able to provide needs, both for the local society and the tourists, which is based on the existing phenomena, so that it will be able to represent the environment of the tourism area of Klayar beach. Keywords: Culture, Phenomenology Architecture, Tourism Area, Resort